Album of prehistoric man - McGowen, Tom.; Ruth, Rod. (Chicago : Rand McNally, 1912)
A brief introduction to the evolution and characteristics of prehistoric people from apelike prehumans to modern man.
Includes index.
Keywords: Prehistoric peoples -- Juvenile literature; Human evolution -- Juvenile literature; Prehistoric peoples; Evolution